Iggy Pop life class - Deller, Jeremy 1966-; Atkins, Sharon Matt (Heni Publishing, 2016)
"In Iggy Pop Life Class, Turner Prize-winning artist Jeremy Deller used the traditional life drawing class to stage a performative event with Iggy Pop as model and subject. The exhibition presents the resulting drawings along with works from our historical collections, chosen by Deller, that depict the male body, examining shifting representations of masculinity throughout history. The fifty-three drawings included in the exhibition were created on February 21, 2016, during a one-day life drawing class, using Pop as the unexpected model. The class was held at the New York Academy of Art and included twenty-two artists drawn from New York City. - Published on the occasion of the exhibition Iggy Pop Life Class at the Brooklyn Museum, November 4, 2016 - March 26, 2017
Keywords: Deller, Jeremy / 1966- / Exhibitions; Pop, Iggy / 1947- / Interviews; Pop, Iggy / 1947- / In art / Exhibitions; Iggy Pop -- Rockmusiker -- 1947-; Deller, Jeremy -- 1966-; Brooklyn Museum / Exhibitions; Figure drawing / Exhibitions; Human figure in art / Exhibitions; Male nude in art / Exhibitions; Aktzeichnung; Ausstellungskatalog; Ausstellungskatalog -- Brooklyn Museum -- 04.11.2016-26.03.2017 -- New York, NY; Interview